L’Australia nelle sue relazioni politiche ed economiche con la Cina: luci e ombre di un rapporto lungo, alterno e complesso - Flavio Lucchesi; Alice Giulia Dal Borgo (Bollettino della Società Geografica Italiana, 2020)
The article reconstructs the evolution of the political and economic relations developed between Australia and China from the birth of the Confederation up to the present day, resuming – according to the Australian perspective – the ranks of the relations that have taken place over time between these two countries, which are extremely different in terms of historical political, social, cultural events. The critical examination of a wide range of English-language literature, produced over time by scholars of various disciplines, aims to understand and discuss the various phases of a comparison that –albeit in alternate, discontinuous, contradictory and sometimes conflictual forms – has always been kept alive. The current situation sees both States strongly linked by a delicate and complex connection of political and economic interests, as well as leading players in the “crowded” and dynamic Asia Pacific region. This set of circumstances poses specific questions to Australia about the future of its bilateral relations with China, which – in a short and medium-term perspective – must not be separated from careful planning that also takes due account of the knowledge of the complex development of past experiences.